1994
DOI: 10.1017/s0022149x00001607
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical localization of key glycolytic and related enzymes in adultOnchocerca fasciata

Abstract: The activities of some key enzymes of the glycolytic and pentose phosphate pathways were investigated histochemically in adult female Onchocerca fasciata (Nematoda: Filarioidea). The distribution patterns of phosphofructokinase (PFK), aldolase (ALD), glyceraldehyde 3-phosphate dehydrogenase (G3PDH) and glucose 6-phosphate dehydrogenase (G6PDH) in different tissues of the worm were determined by employing NitroBlue Tetrazolium (NBT). The glycolytic enzymes PFK, ALD, and G3PDH were distributed throughout the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…(See Barrett 1983 for review). The present and recent histochemistry studies on O. fasciata (Omar and Raoof 1994b) have shown that specific glycolytic and related enzymes are present in different tissues and organs of the worm. In filariae, as in other parasitic helminths, glucose metabolism proceeds via glycolysis as far as the level of phosphoenolpyruvate (PEP; Saz 1981;Barrett 1983;Tielens and Van den Bergh 1985).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…(See Barrett 1983 for review). The present and recent histochemistry studies on O. fasciata (Omar and Raoof 1994b) have shown that specific glycolytic and related enzymes are present in different tissues and organs of the worm. In filariae, as in other parasitic helminths, glucose metabolism proceeds via glycolysis as far as the level of phosphoenolpyruvate (PEP; Saz 1981;Barrett 1983;Tielens and Van den Bergh 1985).…”
Section: Discussionmentioning
confidence: 56%
“…The presence of significant amounts of G-PGDH activity may be taken as an indication of a pentose pathway in adult O. fasciata, especially as the starting enzyme of this pathway, G-6-PDH, has been demonstrated in this filarial worm (Omar and Raoof 1994b). The first two enyzmes of the cycle (G-6-PDH and 6-PGDH), have been characterized biochemically in other filarial worms (Barrett 1983), although their presence does not necessarily mean that the cycle is complete (Barrett 1981).…”
Section: Discussionmentioning
confidence: 89%
“…The cells were then spread on a clean glass slide and dried using a stream of warm air. A silicone grease mixture was used to delimit the area where 200 µl of the reaction mixture, containing twice the enzyme concentrations described above and 1.2 mM 2,2 di‐p‐nitrophenyl‐5,5,‐diphenyl‐3,3‐(3,3‐dmethoxy‐4,4‐diphenylene)‐ditetrazolium chloride (NBT) in addition to the components described in the previous section, were added (e.g., Omar and Raoof, 1994). The reaction was started with 1 mM Fru‐1,6‐P 2 .…”
Section: Methodsmentioning
confidence: 99%